Environmental Management Systems in Public Sector - Waxin, Marie-France (2023)
This chapter focuses on environmental management systems (EMS) in public sector organisations (PSOs). Our objectives are to 1) explain what is an EMS, describe the two main EMS standards (ISO 14001 and EMAS) and how to implement them in PSOs, 2) present the benefits of EMS adoption in PSOs, and 3) present the key factors of successful EMS implementation in PSOs. The major benefits of EMS implementation in PSOs are improved environmental management practices, environmental awareness and image, organizational cost-efficiency, and environmental performance. The major key success factors are management's support, employees' and managers' awareness, competence and involvement, adoption of a collaborative management approach, allocation of sufficient organizational resources, and stakeholder involvement. We conclude by identifying interesting avenues for future research. This chapter will assist EMS scholars and practitioners in better understanding the specific issues related to EMS implementation in PSOs.